2017
DOI: 10.1007/s00702-017-1811-y
|View full text |Cite
|
Sign up to set email alerts
|

Low left amygdala volume is associated with a longer duration of unipolar depression

Abstract: The amygdala plays a crucial role in the pathogenesis of major depressive disorder (MDD). While robust findings support a negative impact of illness duration on hippocampal volume in MDD, morphometric studies of the amygdala have yielded inhomogeneous results. Considering the methodical problems of automatic segmentation methods, a standardized segmentation protocol with proven inter- and intra-rater reliability was employed using high-resolution magnetic resonance imaging. To identify the effect of MDD on amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Human brain imaging studies demonstrate that decreases in brain tissue volume across multiple brain areas correlate with stress-related disorders such as major depressive disorder (MDD; Grieve, Korgaonkar, Koslow, Gordon, & Williams, 2013;Sheline, Wang, Gado, Csernansky, & Vannier, 1996;Zavorotnyy et al, 2018). It was initially proposed that neuronal loss was responsible for this observation in the hippocampus (Sheline et al, 1996).…”
Section: Stress Is Associated With Changes In Glial Density and Mormentioning
confidence: 99%
See 1 more Smart Citation
“…Human brain imaging studies demonstrate that decreases in brain tissue volume across multiple brain areas correlate with stress-related disorders such as major depressive disorder (MDD; Grieve, Korgaonkar, Koslow, Gordon, & Williams, 2013;Sheline, Wang, Gado, Csernansky, & Vannier, 1996;Zavorotnyy et al, 2018). It was initially proposed that neuronal loss was responsible for this observation in the hippocampus (Sheline et al, 1996).…”
Section: Stress Is Associated With Changes In Glial Density and Mormentioning
confidence: 99%
“…The effect of MDD on glial cell density and neuron: glia ratio has also been demonstrated in the amygdala (Bowley, Drevets, Öngür, & Price, 2002), but intriguingly, these effects were observed primarily in the left amygdala (Bowley et al, 2002). Lateralization of the amygdala is a well-described phenomenon and it has been suggested that grey matter volume changes in the left amygdala can be correlated with severity of depression (Zavorotnyy et al, 2018). In the hippocampus, data have been mixed.…”
Section: Stress Is Associated With Changes In Glial Density and Mormentioning
confidence: 99%
“…Generally, neural plasticity in the amygdala (and other brain structures) is thought to be influenced by major depressive disorder and other types of depression in the form of atrophy and apoptosis. Similar to research on the hippocampus, volumetric changes in the amygdala have also been associated with depression in individuals (Zavorotnyy et al, 2018; see also Hastings et al, 2004).…”
Section: Brain Structures and Depressionmentioning
confidence: 59%
“…Specifically, grey matter volume in the amygdala was found to be reduced in individuals with prolonged unipolar depression as compared to individuals with late onset depression. Results of this study suggest that grey matter volume (i.e., neuronal density) shares a negative relationship with prolonged depression, indicating retraction of neuron density, and perhaps neuronal death (Zavorotnyy et al, 2018).…”
Section: Brain Structures and Depressionmentioning
confidence: 69%
See 1 more Smart Citation